Social Museology, Disability and Non-Formal Education: Skills and Learning of People with Intellectual Disabilities at the Museum of Art in Rio (Cadernos de Sociomuseologia, 2021)
The main objective of the research is to analyze how the relationship of the educator, teacher and student contribute to the teaching and learning process, based on non-formal education, addressing a social function of the museum, including People with Intellectual Disabilities. A methodology based on the analysis of the social function of the Museum of Art of Rio - MAR, located in Rio de Janeiro, through the Project Encontro de Saberes, considering three schools, being a private school, Colégio Eduardo Guimarães and two public schools, Municipal School Nicolau Antônio Taunay and Maurício de Medeiros Municipal Special School, located in the city of Rio de Janeiro. To make the records, notes were used in the field notebook, reports from educators, teachers and students about the project, films, photographs and physical record of the activities carried out. We concluded that there was a greater interest by schools in participating in the project, after realizing that the Museum of Art of Rio - MAR had a project with a team specialized in assisting people with disabilities. Keywords: Social Museology; Intellectual Disability; Non Formal Education; MAR.